PENERAPAN TRADISI MBESUR MBESURI DI DESA SUKANALU, KECAMATAN TIGAPANAH, KABUPATEN KARO - Levita Eltriani Sigalingging; Erwita Floureyna Sembiring; Lestari Dara Cinta Utami Ginting; Budi Agustono (Bajang Institute, 2023)
This paper discusses the application of the Mbesur Mbesuri tradition in the Karo community in Sukanalu village today. The Mbesur Mbesuri tradition is a unique tradition from karo origin, namely gratitude and joy for someone who is pregnant by feeding pregnant women delicious food until they are full. The Mbesur Mbesuri tradition has been carried out for a long time and has been passed down from generation to generation to the current generation of Karo people. This paper wants to see how the application of the Mbesur Mbesuri tradition as a hereditary tradition in the life of the Karo community in Sukanalu village today. This study uses historical methods, namely Heuristics, Verification, Interpretation, and Historiography. The results of this study indicate that in the midst of the progress of the times, the implementation of the Mbesur Mbesuri tradition in the Karo community of Sukanalu village is still mostly carried out by the people of Karo district.